Hubungan Ilmu Pengetahuan dan Moralitas: Analisis Problem dan Tanggung Jawab Keilmuan - Wisnu Al Amin; Maria Ulfa (TSAQAFAH, 2018)
Science and technology bring people to a more advanced life. However, this modern life can not be separated from the serious problems that threaten mankind. Technological advances are widely misused so as to cause damage and destruction. Technology that originally aims to solve the problems of mankind, turned into the problem itself. Modern science legitimizes any action in society, even if it is contradict to the values and norms of truth. If examined carefully, this issue departs from the worldview that underlie the science. West and Islam have different ways of understanding the nature of science, its epistemology, and its usefulness. In Islam, the physical and metaphysical felds are indistinguishable, while the West distinguishes them. The West with its secularized worldview regards religious values as unimportant. This is actually inseparable from the trauma of Western society towards religion (Christian) in the past. This article tries to answer the problems posed by modern science. The study of this article begins by discussing what modern science is and its relation to European history. From there the study found that the fundamental problem lies in the realm of philosophy of science. At the end the researcher offers “Islamization or integration” of religion and technology, in answer to the problems posed by modern Western science. From this, it is expected to create a sustainable civilization, because science is no longer a threat to the survival of human life.